Wind characteristics and wind power potential of the Indian summer monsoon - MOOLEY, D. A. (MAUSAM, 1983)
Utilising the hourly wind data for the period 1969-73, characteristics of the monsoon (June-September) wind over Saurashtra-Kutch, Gujarat and penisular India have been brought out. The wind regime over moved Saurashtra-Kutch, adjoining coasts of Gujarat and of Konkan, southern parts of the peninsular India and at into a some stations in Deccan plateau is strong. Marked diurnal variation in wind is experienced at inland stations. Power computations show that a good amount of power exists in the wind over Saurashtra-Kutchand. the adjoining coastal belts in southern part of the peninsula and at a few stations in the Deccan plateau. In particular over and around the Gulf of Kutch, the wind has a high power potential. Wind power over Saurashtra-Kutch and Gujarat in a bad monsoon year need not be less than that during a good monsoon year. The available monsoon wind ported power can be used through a suitably devised windmill for irrigation that may be required by the crops and for drawing water from wells and grinding corn in rural areas.